2019
DOI: 10.1002/cctc.201801934
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Palladium‐Catalyzed Carbocyclization‐Functionalization of Bisallene: A Computational Study

Abstract: Density functional theory calculations were performed to reveal the mechanisms of Pd‐catalyzed cascade carbocyclization‐borylation and arylation reactions. The computational results indicate that the reactions start with allylic C−H cleavage through concerted metalation‐deprotonation and an intramolecular exo‐type allene insertion to form a six‐membered carbocycle intermediate. The regioselectivity of insertion could be explained by frontier molecular orbital theory and natural population analysis calculation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…However, several attempts to locate the transmetalation transition state failed. [ 16 ] Instead, we found that the association of the TFA anion to Pd center would give neutral complex IM5 , which then undergoes the B—B oxidative addition via transition state TS4 to afford Pd(IV) species IM6 , with an energy barrier of 19.7 kcal/mol relative to IM4 . [ 17 ] Although IM6 is relatively unstable, the subsequent C‐B reductive elimination via transition state TS5 was found to be quite facile with an energy barrier of only 5.8 kcal/mol relative to IM6 , leading to very stable Pd(II) intermediate IM7 and final product 2a .…”
Section: Resultsmentioning
confidence: 99%
“…However, several attempts to locate the transmetalation transition state failed. [ 16 ] Instead, we found that the association of the TFA anion to Pd center would give neutral complex IM5 , which then undergoes the B—B oxidative addition via transition state TS4 to afford Pd(IV) species IM6 , with an energy barrier of 19.7 kcal/mol relative to IM4 . [ 17 ] Although IM6 is relatively unstable, the subsequent C‐B reductive elimination via transition state TS5 was found to be quite facile with an energy barrier of only 5.8 kcal/mol relative to IM6 , leading to very stable Pd(II) intermediate IM7 and final product 2a .…”
Section: Resultsmentioning
confidence: 99%
“…The activation barrier of TS -1 is calculated to be 8.8 kcal/mol relative to Int -1 , i.e., 21.3 kcal/mol relative to the Pd­(II) acetate trimer, which constitutes the rate-determining barrier of the reaction (Figure a) . This is consistent with the above KIE experiments for substrate 1a (Scheme ), showing that this step is the rate-limiting step . This step is also the first irreversible step of the reaction as can be seen from Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, M06-L can provide accurate information for reaction systems containing transition metals, and M06-2X has good performance in describing the main-group thermochemistry. To differentiate the two indistinguishable pathways in the coupling of benzoic acid and phenoxy acetylene catalyzed by Ag + , the conventional B3LYP functional [34][35][36][37] was applied to revisit this process at the same basis set level. In addition, frequency verification was performed to judge a transition state or a local minimum according to the number of imaginary frequency (0 or 1).…”
mentioning
confidence: 99%